The Confucian Revival in Taiwan Xu Fuguan and His Theory of Chinese Aesthetics. - Sernelj, Téa (Cambridge Scholars Publisher, 2021)
Xu Fuguan (1904-1982) is one of the central representatives of the second generation of Taiwanese Modern Confucianism. This book focuses primarily on his fundamental contributions to the philosophy of this intellectual current, particularly his reinterpretations and reevaluations of the basic axiological concepts of the original Confucian and Daoist aesthetics. It also addresses issues related to his attempts to preserve, systematize, and modernize traditional Chinese aesthetics. Xu Fuguan's theory of the Chinese ideational tradition is defined by the paradigm of the traditional link between e.